Pengaruh Kinerja Keuangan, Struktur Modal dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Farmasi yang Terdaftar pada BEI Tahun 2013-2017 - Diana Susilowati; H M Saiful Bahri; Elok Dwi Vidiyastutik; Tatik Amani (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2019)
Return On Assets (ROA), Debt to Equity Ratio (DER) and Total Assets on Corporate Values in Registered Pharmaceutical Companies in the Year 2013-2017. Firm value is an assessment or view of a company that is often assumed to be the value of shares so that the company seeks to max. the value of shares to increase the firm value. This research aims to find proof of the effect of Financial Performance (ROA), Capital Structure (DER) and Company Size (Total Assets) on firm value (PBV). This study uses a sample of pharmaceutical companies listed on the Indonesian Stock Exchange in 2013-2017 with a total of 7 companies, using the purposive sampling method. The results showed with a significance level of α = 0.05, it was found that financial performance, capital structure, and company size simultaneously had an effect on the firm value with Fount ˃ Ftable, financial performance variables and capital structure partially had a sig. effect on firm value with count ˃ t table, firm size partially doesn’t have an influence on the firm value. The capital structure variable that has the most dominant influence on firm value, is indicated by the value of Standardized Coefficients Beta 0.897 with count (4.422) greater than the other.